PENDIDIK DALAM BERBAGAI PANDANGAN DAN PROMBLEMATIKA PASCA PANDEMI - Yenti Murni; Wedra Aprison; Afrinaldi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Education is the main road to a prosperous life both in this world and in the hereafter. Education has several important components, one of which is an educator. An educator is the key to the success of an education. Educators have several different meanings from various views. First, in the view of students, the educator is someone who is upheld, imitated and becomes an example for him. Second, in the view of parents of students, an educator is someone who teaches their children at school. Third, in the view of Islam, educators are humans who are given the advantage of having the ability to impart their knowledge to others, even their degrees are raised by Allah SWT. because his profession is very noble. Some of the problems or problems faced by educators, due to the behavior of students when it was still a pandemic and still carried over to this day, are: moral decline, lack of socialization, lack of respect for educators and lack of interest in reading students. Efforts by educators must be made to overcome these problems by strengthening their skills as an answer to these challenges. .Therefore, it is not enough for educators to only be armed with noble character, but educators must be professionals who can integrate the Qur'an with science which is growing rapidly, so that the Qur'an is truly Kalamullah which is always practiced without knowing deadline.